The Effect of Social Networks on Financial Literacy - ÇİLİNGİRTÜRK, AHMET METE (SOSYOEKONOMI SOC, 2019)
Financial literacy demonstrates the ability to make use of rational choices with the use of financial instruments and decision-making systems that are frequently encountered in everyday life. The most important part of the rational consumer or investor assumption is that the information must be fully and evenly distributed. However, today's researches focuse on non-rational behavioral finance models. Increasing financial literacy is important for sustainable household economic management. It is possible to increase the financial literacy with the internet-based social media and applications which affect every part of the society. According to the findings, social networks are a suitable tool for giving education on this subject. However, these results can be attributed to the financial and economic attitudes of the individuals.
Keywords: Financial Literacy; Finance and Economical Attributes Scale; Economic Human Types; Social Networks and Media; BEHAVIOR